2019
DOI: 10.3389/fcimb.2019.00066
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Arginine Regulates Severity of Experimental Colitis and Affects the Colonic Microbiome

Abstract: There is great interest in safe and effective alternative therapies that could benefit patients with inflammatory bowel diseases (IBD). L-arginine (Arg) is a semi-essential amino acid with a variety of physiological effects. In this context, our aim was to investigate the role of dietary Arg in experimental colitis. We used two models of colitis in C57BL/6 mice, the dextran sulfate sodium (DSS) model of injury and repair, and Citrobacter rodentium infection. Animals were given diets cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 62 publications
7
55
2
Order By: Relevance
“…Our studies investigated the role of dietary arginine in the peak of C. rodentium infection in a susceptible murine strain. However, a previous report suggested that supplementation of arginine in the diet decreased pathogen burden, in a less susceptible murine strain at a later time point, close to the resolution of the disease (30). Interestingly, in both our and the previous studies the levels of arginine in the colon remained the same regardless of its presence or concentration in the diet (SI Appendix, Fig.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our studies investigated the role of dietary arginine in the peak of C. rodentium infection in a susceptible murine strain. However, a previous report suggested that supplementation of arginine in the diet decreased pathogen burden, in a less susceptible murine strain at a later time point, close to the resolution of the disease (30). Interestingly, in both our and the previous studies the levels of arginine in the colon remained the same regardless of its presence or concentration in the diet (SI Appendix, Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, in both our and the previous studies the levels of arginine in the colon remained the same regardless of its presence or concentration in the diet (SI Appendix, Fig. S7) (30). However, arginine dietary differences impacted the levels of this amino acid in the serum under homeostasis, and its levels were enhanced in both the colon and serum upon the onset of inflammation due to dextran sulfate sodium treatment (30).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Correspondingly, its high intake has been linked with restored microbial diversity in the gut, specifically, with an increased prevalence of Bacteroidetes. Consequently, arginine supplementation has led to improved histology and reduced bowel shortening while supplementation with proline or ornithine, amino acids downstream of arginine, had no effect [57].…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic consumption of l-arginine promotes colitis. Recently, oral l-arginine supplementation of DSS-treated mice was found to improve the course of colitis (59,60) and to enhance intraluminal and systemic polyamine concentrations (61). Here, we tested to determine whether dietary l-arginine restriction reversed the improved outcome of DSS-induced colitis in Tie2-Cre Arg1 fl/fl mice.…”
Section: Figure 2 Intestinal Microbiota and Il-4/il-13 Promote Arg1mentioning
confidence: 97%